2015
DOI: 10.1152/jn.00373.2014
|View full text |Cite
|
Sign up to set email alerts
|

In vivo electrophysiological recordings in amygdala subnuclei reveal selective and distinct responses to a behaviorally identified predator odor

Abstract: Govic A, Paolini AG. In vivo electrophysiological recordings in amygdala subnuclei reveal selective and distinct responses to a behaviorally identified predator odor. J Neurophysiol 113: 1423-1436, 2015. First published December 4, 2014 doi:10.1152/jn.00373.2014.-Chemosensory cues signaling predators reliably stimulate innate defensive responses in rodents. Despite the well-documented role of the amygdala in predator odor-induced fear, evidence for the relative contribution of the specific nuclei that compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
1
21
1
Order By: Relevance
“…The amygdala mediates fear and defensive behaviour in rodents in response to predator odour . The MeA is the first site of convergence of olfactory and vomeronasal information and exhibits a robust response to cat odour . However, it is not clear how predator odour signals activate the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amygdala mediates fear and defensive behaviour in rodents in response to predator odour . The MeA is the first site of convergence of olfactory and vomeronasal information and exhibits a robust response to cat odour . However, it is not clear how predator odour signals activate the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a differential modulatory role for these two amygdala nuclei in terms of stress‐induced suppression of pulsatile luteinising hormone (LH) secretion, with the MeA being more responsive to psychological stress and the CeA to physiological stress . Recent in vivo electrophysiological studies in rats have demonstrated that the MeA had the highest frequency of response and distinct firing pattern to predator urine compared to other amygdaloid nuclei, which confirms the importance of this neurocircuitry in psychological stress. Moreover, lenti‐viral overexpression of CRF in the CeA in pre‐pubertal female rats, mimicking the effect of chronic stress, disrupts reproductive function and leads to irregular oestrous cycles, increased anxiety and advanced puberty .…”
Section: Introductionmentioning
confidence: 92%
“…Although neurons in plCoA have been shown to respond to odorants, their tuning properties have not yet been defined (Bergan et al, 2014; Govic and Paolini, 2015; Root et al, 2014; Staples et al, 2008). The plCoA receives input from both the olfactory bulb and the PCx, and harbors intrinsic associational connections that distribute information locally (Price, 1973; Schwabe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The male (mFGS) signal in a third species, mandarin voles, failed to significantly activate medial amygdala, possibly reflecting social structure differences from other rodents (He et al 2014). Threatening heterospecific (cat; predator) stimuli generally activate ventral MeP in mice (Samuelsen and Meredith 2009b, 2011; Perez-Gomez et al 2015) and rats and are avoided by both species (Dielenberg et al 2001; Govic and Paolini 2014). In mice, Carvalho et al did not find a predominant ventral activation in mice by predator stimuli, nor any general distinction between areas activated by conspecific stimuli as a class (pooled data for male and female stimuli) compared to heterospecific stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…These signals must be distinguished from each other and from potentially similar signals of other species. In rodents, many conspecific and heterospecific chemical communication signals (including pheromones) are detected by the vomeronasal, or accessory-olfactory, system (Scalia and Winans, 1975; Johnston, 1998, Samuelsen and Meredith 2009b, Kaur et al 2014, Dey et al 2015) - but the main olfactory system can also detect some chemosignals used for communication (Meredith 1998, Schaal et al 2003, Baum and Kelliher 2009, Matsuo et al 2015 Govic and Paolini 2015, Perez-Gomez-et al 2015), possibly including some non-volatile stimuli (Spehr et al 2006). Both systems send afferent inputs to the amygdala which terminate mainly in separate, but adjacent nuclei (Cadiz-Moretti et al 2014, Perez-Gomez et al 2015).…”
mentioning
confidence: 99%